Cevaplar

2012-10-25T22:00:36+03:00

(-8)(-3)(-12)(+3)(+8)=(-23)(+11)=(-12)=B

 

(+4)(+2)(+6)(+3)=(15)=B

 

(-16)(+8)(+4)(-12)(+2)=(-28)(+14)=(-14)=D 

1 5 1
2012-10-25T22:05:25+03:00

1= b)-12       cözüm:      -8+-3=-11-12=-23-(-3)=-20+8=-12

2= b)15          cözüm:  4+2=6-(-6)=12-(-3)=15

3= d)-14         cözüm:  -16+8=-8 - (-4)=-4-12= -16+2=-14  çok uğrastım yazmak için bari en ii secc:)                                                    

1 5 1
2012-10-25T22:05:32+03:00

1= b)-12       cözüm:      -8+-3=-11-12=-23-(-3)=-20+8=-12

2= b)15          cözüm:  4+2=6-(-6)=12-(-3)=15

3= d)-14         cözüm:  -16+8=-8 - (-4)=-4-12= -16+2=-14  çok uğrastım yazmak için bari en ii secc:)                                                    

1 5 1